2008
DOI: 10.1021/ja801466t
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Structure, and Reactivity of Nonstabilized Organoiron Compounds. Implications for Iron-Catalyzed Cross Coupling Reactions

Abstract: A series of unprecedented organoiron complexes of the formal oxidation states -2, 0, +1, +2, and +3 is presented, which are largely devoid of stabilizing ligands and, in part, also electronically unsaturated (14-, 16-, 17- and 18-electron counts). Specifically, it is shown that nucleophiles unable to undergo beta-hydride elimination, such as MeLi, PhLi, or PhMgBr, rapidly reduce Fe(3+) to Fe(2+) and then exhaustively alkylate the metal center. The resulting homoleptic organoferrate complexes [(Me 4Fe)(MeLi)][L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
309
2
23

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(346 citation statements)
references
References 187 publications
11
309
2
23
Order By: Relevance
“…Fürstner and co-workers showed that Fe-"ate" complexes, in which the formal oxidation states of Fe range from -2 to +2, might be catalytically active; 8,15 treatment of FeCl 3 with a large excess of aryl Grignard reagents could lead to Fe(0)-"ate" species. 8 Further, they showed that a formal Fe(-2) complex,…”
Section: Introductionmentioning
confidence: 99%
“…Fürstner and co-workers showed that Fe-"ate" complexes, in which the formal oxidation states of Fe range from -2 to +2, might be catalytically active; 8,15 treatment of FeCl 3 with a large excess of aryl Grignard reagents could lead to Fe(0)-"ate" species. 8 Further, they showed that a formal Fe(-2) complex,…”
Section: Introductionmentioning
confidence: 99%
“…[11] The Fe III -C bonds in N-heterocyclic carbene complexes are even longer, for example, the Fe-CH 3 Scheme 3. Palladium(II) chloride did not rearrange the mesityl ligand to form a heterodinuclear species but resulted in the oxidized aryliron complex 5. distances are 2.060(11) Å in the 17-valence-electron iron(III) complex [Cp*Fe(η 3 -C 3 H 5 )(CH 3 )] [12] and 2.090(2) Å in the 1,3-diisopropylimidazol-2-ylidene complex of iron(III) chloride. [13] The tert-butyl substituent of C-4 is located directly above the mesityl moiety and bent out of the plane of the cyclopentadienyl ring by ca.…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic efficiencies of iron salts in Kumada cross coupling reactions of Grignard reagents with aryl or alkyl halides have been demonstrated previously [13,[44][45][46][47]. However, investigations of Kumada coupling catalyzed by a welldefined iron-NHC complex are rare.…”
Section: Catalytic Kumada Coupling Reactionsmentioning
confidence: 99%